Extraction and isolation of Ovine Pregnancy-Associated Glycoprotein (ovPAG) from cotyledon placenta of Garut sheep - E.T. Setiatin; D. Sajuthi; B. Purwantara; C. Talib (Indonesian Center for Animal Research and Development (ICARD), 2009)
Pregnancy-associated glycoprotein (PAG) structurally related to aspartic protease, expressed in the outer epithelial cell layer (trophectoderm) of ungulate placenta. Ovine PAG (ovPAG) synthesized by mono- and binucleic trophoblast before complete implantation at Day 14-15. Of this, ovPAG could be used as a marker for early pregnancy. The objective of study was to extract and isolate PAG from placenta of Garut Sheep collected at term and to characterize their molecular weight. The procedures included extraction of protein at neutral pH (cotyledon was thawed, minced, added PBS, blended and centrifuged), acidic (H3PO41M, pH 4,5; centrifuged) and ammonium sulfate (40% and 80% (NH4)SO4, centrifuged) precipitation; gel filtration (Sephadex-G75), anion exchange chromatography (DEAE- cellulose). Cotyledon extract was subjected to Sephadex-G75 and DEAE cellulose, and their fractions were measured their absorbances. Absorbances of Sephadex-G75 and DEAE fractions at peak were assayed for protein concentration (Bichinconinic protein assay). Continuously, these fractions were subjected to monogel SDS-PAGE and stained by Commassie Brilliant Blue. It was four different molecular weights isolating from cotyledon of Garut Sheep, namely 68.8, 36.04, 32.39 and 12.18 kDa. However, after chromatography anion exchange (DEAE-cellulose), only three bands exist, those were 71,67; 33,64 and 30,86 kDa. Key words: Garut sheep, Pregnancy-Associated Glycoprotein (PAG), Cotyledone, SDS-PAGE, DEAE-cellulose